Politics of Representation: A Comparative Study of Our Moon Has Blood Clots and Curfewed Night - Sharma, Pummy (Integrated Journal for Research in Arts and Humanities, 2023)
This article combines the approaches of New Historicism and comparative studies to analyse the Curfewed Night by Basharat Peer and Our Moon Has Blood Clots by Rahul Pandita. Published two years apart, these books recount the turbulent years in Kashmir from the mid-1980s to the late 1990s. Even a superficial glance makes it clear that these books view these events from different narrative and ideological perspectives. New Historicists emphasise that history is not a series of objective truths and that multiple viewpoints exist at any given point in history. As a result, they focus on what interpretations of history tell us about the interpreters. At the same time, the recollection of traumatic events raise serious questions about the accuracy and authenticity of a particular account. Under these considerations, this research article attempts to reveal the politics of representation and the ideological and political goals of the authors.